Art and Citizenship in Prison Context (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This text traces a brief trajectory a prison theatre workshop called PELE, developed in Portugal in recent years. The projects presented are Sign in, developed with men in the Porto Prison, and Unforgettable Emília in the Santa Cruz do Bispo Prison for women. Finally, the article discusses the ECOAR project supported by the Active Citizenship Gulbenkian Foundation. This article describes an artistic practice that integrates the dimension of citizenship in prison contexts.
Keywords: Art; Citizenship; Prison; Project